Verification of expression of LINC00648 in the serum of lung cancer patients by TCGA database - Zhao, Ling; Gao, Mingxu; Zhao, Xiujuan (Cellular and Molecular Biology, 2020)
TCGA data were used to verify the expression of LINC00648 in lung cancer patients to provide a reference for clinical practice. Lung cancer transcriptome data were downloaded by the TCGA database and LINC00648 data were extracted for analysis. Fifty-two patients with lung cancer diagnosed in our hospital from May 2014 to March 2016 were collected as the patient group and 30 normal people as the control group. RT-qPCR was used to detect the expression of LINC00648 in serum, follow up of patients was carried out, and bioinformatics was used to analyze the potential mechanism of LINC00648. LINC00648 was highly expressed in lung cancer. Lymphatic metastasis and probability of low differentiation were significantly increased, and the overall survival rate of highly expressed patients with lung cancer was reduced and the prognosis was poor. LINC00648 had 17 potential miR-targeted and 78 miR-targeted mRNAs. LINC00648 was found to have participated in SMAD binding, transcriptional activator activity, RNA polymerase II transcription regulatory region sequence-specific DNA binding, PDZ domain binding, cytokine binding, activin binding, RNA polymerase II activating transcription factor binding, transforming growth factor-beta receptor binding, etc. LINC00648 participated in the signal pathways of the Hippo signaling pathway, Transcriptional misregulation in cancer, MAPK signaling pathway, Proteoglycans in cancer. There were 55 co-expression pairs in PPI protein co-expression analysis, of which KIF11 was the most common. High expression of LINC00648 in lung cancer patients indicates poor prognosis of patients and is expected to become a potential diagnostic marker for lung cancer.